2018
DOI: 10.1021/jacs.7b13361
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Defined Antibody– and Small Molecule–Drug Conjugates for in Vivo Tumor Targeting Applications: A Comparative Analysis

Abstract: We present the first direct comparative evaluation of an antibody-drug conjugate and of a small molecule-drug conjugate for cancer therapy, using chemically defined products which bind with high-affinity to carbonic anhydrase IX, a marker of tumor hypoxia and of renal cell carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
161
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(165 citation statements)
references
References 48 publications
3
161
0
1
Order By: Relevance
“…However, it is important to note that the total accumulation of anticancer drugs into tumors may not directly reflect the anticancer efficacy. For instance, in a recent study, it was reported that antibody–drug conjugates with low accumulation in tumors demonstrated better therapeutic effect than small molecule–drug conjugates achieving higher tumor accumulation . Both the antibody–drug conjugate and the small molecule–drug conjugate comprised the anticancer drug monomethyl auristatin E (MMAE) linked to the ligand via a cathepsin B cleavable peptide linker.…”
Section: Targeting Strategies With Ligand‐installed Nanocarriersmentioning
confidence: 99%
“…However, it is important to note that the total accumulation of anticancer drugs into tumors may not directly reflect the anticancer efficacy. For instance, in a recent study, it was reported that antibody–drug conjugates with low accumulation in tumors demonstrated better therapeutic effect than small molecule–drug conjugates achieving higher tumor accumulation . Both the antibody–drug conjugate and the small molecule–drug conjugate comprised the anticancer drug monomethyl auristatin E (MMAE) linked to the ligand via a cathepsin B cleavable peptide linker.…”
Section: Targeting Strategies With Ligand‐installed Nanocarriersmentioning
confidence: 99%
“…Die antikörperbasierte selektive Zufuhr von immunstimulierenden Wirkstoffen an die Tumorstelle ist für therapeutische Anwendungen außerordentlich attraktiv, da sie die Kraft des Immunsystems nutzen und mit anderen Anti‐Krebs‐Modalitäten kombiniert werden können. Er gab auch Einblicke in die Erzeugung großer kodierter kombinatorischer Bibliotheken von Antikörpern und kleinen organischen Molekülen (DNA‐kodierte Chemie), sowie in die ligandenbasierte Abgabe von zytotoxischen Wirkstoffen an solide Tumore (niedermolekulare Wirkstoffkonjugate) …”
Section: Sonntag 5 Maiunclassified
“…The antibody‐based selective delivery of immunostimulatory agents to the tumor site is exceptionally attractive for therapeutic applications, since they exploit the power of the immune system and as they can be combined with other anti‐cancer modalities. He also gave insights into the generation of large encoded combinatorial libraries of antibodies and of small organic molecules (DNA‐encoded chemistry), as well as the ligand‐based delivery of cytotoxic agents to solid tumors (small molecule–drug conjugates) …”
Section: Sunday 5 Th Of Maymentioning
confidence: 99%